Ultrasound-Assisted versus Endoscopic Nasojejunal Tube Placement for Acute Pancreatitis: A Retrospective Feasibility Study - Gang Li; Jiajia Lin; Yang Liu; Qi Yang; Zhihui Tong; Lu Ke; Weiqin Li (Gastroenterology Research and Practice)
Objective. The optimal technique for nasojejunal tube (NJT) placement in terms of facilitating early enteral nutrition (EN) in patients with acute pancreatitis (AP) is unclear. In this study, we aimed to evaluate the impact of two common techniques on EN implementation and clinical outcomes in a group of AP patients. Methods. This is a retrospective study. All the data were extracted from an electronic database from August 2015 to October 2017. Patients with a diagnosis of AP requiring NJT placement were retrospectively analyzed. The primary outcome was the successful procedural rate. Results. A total of 53 eligible patients were enrolled, of whom 30 received an ultrasound-assisted technique and the rest received the endoscopy method (n=23). There was no difference in success rates of initial placement procedures between the two groups (93.3% and 95.7% in the ultrasound-assisted group and endoscopy group, respectively). The mean amount of EN delivery within the first three days after NJT placement was significantly higher in the ultrasound-assisted group (841.4 kcal (95% CI: 738.8, 944 kcal) vs. 652.5 kcal (95% CI: 562.5, 742.6 kcal), P=0.018). Moreover, a slight increased postprocedural intra-abdominal pressure (IAP) was observed in patients undergoing endoscopic procedures, but not in the ultrasound-assisted group, especially at 6 hours after NJT placement (0.35 vs. -2.01 from baseline, P<0.05). For clinical outcomes, we observed no difference between groups. Conclusion. Compared with endoscopic procedures, ultrasound-assisted NJT placement possesses the acceptable success rates of initial placement procedures.